2007
DOI: 10.1177/000494410705100302
|View full text |Cite
|
Sign up to set email alerts
|

Successful School Leadership: What is it and Who Decides?

Abstract: Arguments presented in this paper and the evidence from the Tasmanian Successful School Principals Project support broadening what counts for successful schools and school leadership. This broadening needs to embrace student outcomes, including non-cognitive social outcomes such as student empowerment. In examining who should provide the evidence for successful school leadership the need for triangulation, that is, multiple sources of evidence, became clear. Research employing only principal perceptions of suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Gurr et al (2003) also noted that the principal of the institution has an indirect impact on the results of the students working with others and using a series of interventions in terms of developing individual and scholastic skills, as well as teaching and learning. The purpose of organizational learning was related to the leadership practices of successful leaders that included the provision of individual support, the development of a culture of trust, a shared decisionmaking process and distributed leadership, the development of shared objectives and vision, and the high student"s expectations (Mulford et al, 2007;Silins & Mulford, 2002;Leithwood & Hallinger, 2002;Mulford et al, 2004;Mulford & Silins, 2003). Teachers come to school in time regularly.…”
Section: Discussion:-mentioning
confidence: 99%
“…Gurr et al (2003) also noted that the principal of the institution has an indirect impact on the results of the students working with others and using a series of interventions in terms of developing individual and scholastic skills, as well as teaching and learning. The purpose of organizational learning was related to the leadership practices of successful leaders that included the provision of individual support, the development of a culture of trust, a shared decisionmaking process and distributed leadership, the development of shared objectives and vision, and the high student"s expectations (Mulford et al, 2007;Silins & Mulford, 2002;Leithwood & Hallinger, 2002;Mulford et al, 2004;Mulford & Silins, 2003). Teachers come to school in time regularly.…”
Section: Discussion:-mentioning
confidence: 99%
“…The whole school community may also be involved in the assessment of the strategic plan, and in the identification of its strengths and weaknesses. Similarly, Mulford and Grady (2001) and Mulford et al (2007) argue that parents want to be involved in schools -and particularly in school decision making. Better appreciation of systems and of all stakeholders leads to more appropriate actions.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the exposure of the child to the school education and ambience as an early experience has a formative role to play in shaping his future orientation. In fact, the nature and quality of value orientations introduced at the school education depends a lot on the personified leadership agenda and behaviours exhibited by the school principals (Davies 2002;Greenfield 2004;Branson 2007;Mulford et al 2007;Easley 2008;Murphy et al 2009;Harris 2012). It has also been observed that the lack of comprehensive evaluation and generating a need for empirical examination of the virtuous leadership behaviour of school principals especially in Indian context has remained grossly under represented as an area of research.…”
Section: Six Cardinal Virtuesmentioning
confidence: 99%